Much ado about flu: A mixed methods study of parental perceptions, trust and information seeking in a pandemic. Issue 4 (13th March 2018) - King, Catherine L.; Chow, Maria Y. K.; Wiley, Kerrie E.; Leask, Julie
Abstract : Background: Effective public health messaging is essential in both the planning phase and duration of a pandemic. Objectives: This study aimed to gain an understanding of parental information seeking, trusted sources and needs in relation to pandemic influenza A 2009 (pH1N1) to inform future policy planning and resource development. Patients/Methods: We conducted a mixed methods study; parents from 16 childcare centres in Sydney, Australia, were surveyed between 16 November and 9 December 2009, and interviews were conducted with participants from six childcare centres between June 2009 and May 2011. Results: From 972 surveys distributed, 431 were completed; a response rate of 44%. Most parents (90%) reported that doctors were "trusted a lot" as a source of influenza information, followed by nurses (59%), government (56%) and childcare centres (52%). Less trusted sources included media (7% selected "trusted a lot"), antivaccination groups (6%) and celebrities (1%). Parents identified a range of key search terms for influenza infection and vaccine. From 42 in‐depth interviews, key themes were as follows: "Action trigger, " "In an emergency, think Emergency, " "Fright to hype" and "Dr Google and beyond." Parents relied heavily on media messages, but cynicism emerged when the pandemic was milder than expected. Parents viewed a range of information sources as trustworthy, including doctors, authoritative hospital or government websites, and childcare centres and schools. Conclusions: A user‐centred orientation is vital for pandemic communications including tailored information provision, via trusted sources based on what parents want to know and how they can find it.